2006
DOI: 10.1007/s00296-006-0159-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor receptor 2 M196R polymorphism in rheumatoid arthritis and osteoarthritis: relationship with sTNFR2 levels and clinical features

Abstract: We investigate the clinical association of tumor necrosis factor receptor 2 (TNFR2) M196R polymorphism with rheumatoid arthritis (RA) and knee osteoarthritis (OA). Acute phase reactants, lipid profile, sTNFR2 levels, disease activity-disability indexes, and TNFR2 M196R polymorphism were analyzed in 50 RA, 50 knee OA patients, and 120 healthy subjects (HS). The M/M genotype frequency was 0.74 (RA), 0.80 (OA), and 0.64 (HS). The M/R genotype frequency was RA (0.26), OA (0.20), and HS (0.29). The R/R genotype was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…However, the actions of TNF-α are mediated through binding to TNFR2. A genetic abnormality of cytokine regulation that may play a role in the pathophysiology of acne has been examined in a series of studies [16,17,28] , further exploring the TNFR2 gene polymorphisms which affect the production of inflammatory mediators. Peral's [16] results have suggested that the TNFR2 genotype may influence hyperandrogenism and PCOS, further supporting the contribution of inflammatory cytokines to the pathogenesis of acne.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the actions of TNF-α are mediated through binding to TNFR2. A genetic abnormality of cytokine regulation that may play a role in the pathophysiology of acne has been examined in a series of studies [16,17,28] , further exploring the TNFR2 gene polymorphisms which affect the production of inflammatory mediators. Peral's [16] results have suggested that the TNFR2 genotype may influence hyperandrogenism and PCOS, further supporting the contribution of inflammatory cytokines to the pathogenesis of acne.…”
Section: Discussionmentioning
confidence: 99%
“…The TNFR2 mediates most of the metabolic effects of TNF-α. Some studies have proposed that the M196R (676 T→G) variant in exon 6 of TNFR2 is associated with hyperandrogenism [16] , polycystic ovary syndrome (PCOS) [16] , rheumatoid arthritis and osteoarthritis [17] , and SLE [18] etc., further suggesting the role of inflammatory cytokines such as TNFR2 in the pathogenesis of the inflammation-and immune-related diseases.…”
mentioning
confidence: 99%
“…However, the actions of TNF-α are mediated by binding to TNFR2. A genetic abnormality of TNFR2 regulation that may play a role in the pathophysiology of acne has been examined in a series of studies [16,17,28], further exploring the TNFR2 gene polymorphisms which affect the production of inflammatory mediators [16,17,57]. The results of Peral et al [16] suggest that the TNFR2 genotype may influence hyperandrogenism and polycystic ovary syndrome, further supporting the contribution of inflammatory cytokines to the pathogenesis of acne.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have proposed that the M196R (676 T→G) variant in exon 6 of TNFR2 is associated with e.g. hyperandrogenism [16], polycystic ovary syndrome [16], rheumatoid arthritis and osteoarthritis [17] or systemic lupus erythematosus [18], further suggesting the role of inflammatory cytokines such as TNFR2 in the pathogenesis of these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that single-nucleotide polymorphisms (SNP) or elevated plasma levels are associated to some degree with the risk and clinical outcome of some subtypes of lymphomas, solid tumors, and autoimmune diseases such as rheumatoid arthritis or allergy/asthma (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%